PENINGKATAN PENGETAHUAN PENGAWASAN LAPANGAN BAGI SISWA SEKOLAH MENENGAH KEJURUAN - Irika Widiasanti Widiasanti; Santoso Sri Handoyo; Achwan Wirayudha Wirayudha (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract Supervision is an important stage in construction work. The quality of construction is largely determined by the quality of supervision at each stage of work in the field. The problem is that this field supervision process is sometimes neglected, due to: (1) the assumption that the contractor (contractor) of the work is considered experienced, so they are accustomed to doing construction work- (2) there is no, or no attention to the work plan and requirements (RKS), and (3 ) does not exist, or the procedures for carrying out the work are not observed. This service activity aims to provide knowledge related to field supervision in the construction sector for Vocational High School (SMK) students through training. The activity was carried out at SMK Negeri 1 Cikarang Barat, especially the Construction and Property Technology Expertise Program. The construction field supervision training was carried out online using Zoom-meeting, including the presentation of field supervisor materials followed by interactive discussions to share experiences. The training materials distributed were about the implementation of foundation work, beams, plates and columns. The results of the activity evaluation showed that the training process, the benefits of the training, and the presenters had delivered the material well and could be accepted by students. This is known from the evaluation of the post-test results against the pre-test results. Abstrak Pengawasan merupakan merupakan tahapan penting dalam pekerjaan konstruksi. Kualitas konstruksi sangat ditentukan oleh kualitas pengawasan setiap tahapan pekerjaan di lapangan. Permasalahannya proses pengawasan lapangan ini, terkadang terabaikan, dikarenakan: (1) anggapan pelaksana (pemborong) pekerjaan dinilai sudah berpengalaman, sehingga terbiasa mengerjakan pekerjaan konstruksi- (2) tidak ada, atau tidak diperhatikan rencana kerja dan syarat (RKS), dan (3) tidak ada, atau tidak diperhatikan prosedur pelaksanaan pekerjaan. Kegiatan pengabdian ini bertujuan untuk memberikan pengetahuan terkait pengawasan lapangan bidang konstruksi bagi siswa Sekolah Menengah Kejuruan (SMK) melalui pelatihan. Kegiatan dilakukan di SMK Negeri 1 Cikarang Barat khususnya Program Keahlian Teknologi Konstruksi dan Properti. Pelatihanpengawasan lapangan bidang konstruksi dilakukan secara online dengan menggunakan Zoom-meeting, meliputi penyajian materi pengawas lapangan dilanjutkan dengan diskusi interaktif untuk berbagi pengalaman. Materi pelatihan yang dibagikan adalah mengenai pelaksanaan pekerjaan pondasi, balok, pelat dan kolom. Hasil evaluasi kegiatan diketahui bahwa proses pelatihan, manfaat pelatihan, dan pemateri telah menyampaikan materi dengan baik dan dapat diterima oleh siswa. Hal ini diketahui dari evaluasi hasil post-test terhadap hasil pre-test.